Regarding "Chat Reference Service: An Analysis of One Semester's Data" (Fall 2001). - Bruce Slutsky (Issues in Science and Technology Librarianship)
This letter responds to the article "Chat Reference Service: An Analysis of One Semester's Data" (ISTL no. 32, Fall 2001) by JoAnn Sears.